Lifestyles Under Lockdown: A Scoping Review of International Studies on Type 2 Diabetes Self-Management Behaviors During COVID-19 - Cummings, Caroline; Seng, Kagnica; Tweet, Ryan; Wagner, Julie (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background The effect of the COVID-19 pandemic on diabetes self-management behaviors is unclear. Objectives This paper is a scoping review of studies examining health behaviors among people with type 2 diabetes during the COVID-19 pandemic. Eligibility Criteria We searched articles available in English using the Search terms “COVID” and “diabetes”, and, separately, each of the following terms: “lifestyle”, “health behavior”, “self-care”, “self-management”, “adherence”, “compliance”, “eating”, “diet”, “physical activity”, “exercise”, “sleep”, “self-monitoring of blood glucose”, or “continuous glucose monitoring”. Sources of Evidence We searched PubMed, PsychInfo, and Google Scholar databases from December 2019 through August 2021. Charting Methods Data were extracted by 4 calibrated reviewers and study elements were charted. Results The search identified 1,710 articles. After screening for relevance and eligibility, 24 articles were included in this review. Findings show the strongest evidence for reduced physical activity and stable glucose monitoring and substance use. There was equivocal evidence for deleterious changes in sleep, diet, and medication intake. With one minor exception, there was no evidence for favorable changes in health behaviors. Limitations of the literature include small samples, predominantly cross-sectional study designs, reliance on retrospective self-reports, sampling through social media, and few standardized measures. Conclusions Early studies of health behaviors among people with type 2 diabetes during the COVID-19 pandemic suggest a need for novel interventions to support diabetes self-management, especially targeting physical activity. Future studies should go beyond documenting changes in health behaviors and examine predictors of change over time.